Formant analysis of single vowels in Mandarin spoken by Chinese female speakers - Berutu, Elvi Jesica; Febrina, Wardani; Tengku Syarfina; Jelly Prima Silaban (International Journal of Culture and Art Studies, 2026)
This study aimed to investigate the formant measurement of single vowel sounds in the Mandarin spoken by Chinese female speakers. This study employed the audio method. The data were collected from five Chinese female speakers after receiving instructions on the purpose of recording the Mandarin words ending in 7 distinct vowels: a[A], o[o], e[ɣ], ê[ɛ], i[i], u[u], and ü[y]. The audio were directly recorded into the computer, assigning a single file to each set of words from the sources. We used Praat software to extract the first (F1) and second (F2) formants from the data. Presenting the results in the form of numerical tables. The study's findings indicate a significant difference in their voice quality, despite the fact that they are all Chinese. Specifically, they produced the highest formant value for the single vowel [A] in the word "pà," and the longest duration for a Chinese female's pronunciation of the single vowel /o/ was 0.438750 seconds in the word "bo." Meanwhile, the pitch score was lowest for both native speakers and is found in the single vowel /u/ in the word 须 "Xue." The effect of pitch errors is one factor that affects the resulting formant and duration value.